2023
DOI: 10.3390/ma16093518
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Mechanical Properties and Microstructures of Cenosphere Concrete

Abstract: The most valuable components of coal fly ash are cenospheres. Cenospheres are hollow spherical particles produced during the coal-burning processes. As a result of their excellent characteristics, such as high workability, high heat resistance, low bulk density, and high strength, cenospheres can be used in the manufacturing of lightweight cement concrete. The research efforts and outcomes are to produce long-lasting cement-based lightweight concrete (LWC) composites with good mechanical properties. The novelt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 61 publications
(85 reference statements)
0
10
1
Order By: Relevance
“…This image demonstrates the uneven morphology of the cement grains. In their investigations, Lija et al [ 34 , 40 ], Karmegam and Kalidass [ 36 ], and I. Mormol et al [ 41 ] all found the same morphology and existence of components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This image demonstrates the uneven morphology of the cement grains. In their investigations, Lija et al [ 34 , 40 ], Karmegam and Kalidass [ 36 ], and I. Mormol et al [ 41 ] all found the same morphology and existence of components.…”
Section: Resultsmentioning
confidence: 99%
“…In the mixtures, 5%, 10%, 15%, and 20% of the cement content was replaced by granite pulver by mass with the addition of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, and 1.0% of super absorbent polymers by volume fraction. Lija et al [ 34 ], Deepankarkumar et al [ 35 ], and Karmegam and Kalidass [ 36 , 37 ] emphasized the importance of particle packing and specific gravity in determining the mix proportion.…”
Section: Methodsmentioning
confidence: 99%
“…By subjecting fibers to different treatments, it is possible to transit their hydrophilic nature to hydrophobic, resulting in improved performance and easier disposal [9][10][11]. Studies in the literature demonstrate that alkali treatment has caused notable changes in the mechanical properties of reinforcements [12][13][14][15]. Specifically, alkali-treated Borassus fruit fibers exhibited significant increase of 41% in tensile strength, 69% in modulus and 40% in elongation [16].…”
Section: Introductionmentioning
confidence: 99%
“…After curing in hot water, the sintered fly ash aggregate concrete mix containing it showed 62% more compressive strength. Sintered fly ash aggregates have a higher water absorption rate and a specific gravity that is 16 to 46% lower than traditional aggregates [30]. Sintered fly ash aggregate concrete has compressive strengths varying between 27 and 74 Mpa and a density varying between 1651 and 2017 kg/m 3 .…”
Section: Introductionmentioning
confidence: 99%